Purificação, caracterização bioquímica e estrutura primária parcial de uma lectina da esponja marinha Aplysina cauliformis - Viana, Lucas Alecrim Amorim (2021)
Since the first reports of erythrocyte agglutination in the late nineteenth century, several studies on lectins have been carried out. Currently, lectins are considered proteins or glycoproteins, not immunoglobulins, which recognize carbohydrates without participating in the metabolism of ligands. The functions of these proteins are broad, acting mainly on the innate immune system in animals. Animal lectins can be classified into several families according to their structural characteristics. In sponges, lectins belonging to three families, C-type lectins, galectins and tachylectins have already been reported, and the vast majority of lectins isolated from sponges lack structural information to classify them in some group. Among the lectins that do not belong to a family are those extracted from the sponges Aplysina fulva and A. lactuca. These lectins demonstrate biotechnological potential due to antibiofilm activity against certain bacterial strains. Thus, the objective of the work is to extract, purify, characterize, and verify the biological activity of a lectin from Aplysina cauliformis. The combination of chromatographic techniques of affinity, ion exchange and molecular exclusion proved to be efficient in the purification of ACL. The new lectin has been shown to have a high specificity for certain glycoproteins, in particular porcine stomach mucin. The hemagglutinating activity was stable up to 80 °C, and between pH 9 and 10, the presence of divalent cations not being necessary to observe it. In the electrophoresis gel, ACL showed a band of approximately 66 kDa under nonreducing conditions and two bands of approximately 35 kDa under reducing conditions. By molecular exclusion chromatography it was possible to detect and separate two lectins, ACL-1 and ACL-2 with native masses of 145 kDa and 120 kDa, respectively. ACL was subjected to protein digestion and the generated peptides were analyzed by mass spectrometry. However, these peptides showed no similarity to any known protein. Furthermore, ACL was able to agglutinate E. coli bacteria.